Direct Observation of Self‐Organized Water‐Containing Structures in the Liquid Phase and Their Influence on 5‐(Hydroxymethyl)furfural Formation in Ionic Liquids. (6th January 2016) - Kashin, Alexey S.; Galkin, Konstantin I.; Khokhlova, Elena A.; Ananikov, Valentine P.
Abstract: Water‐containing organic solutions are widespread reaction media in organic synthesis and catalysis. This type of multicomponent liquid system has a number of unique properties because of the tendency for water to self‐organize in mixtures with other liquids. The characterization of these water domains is a challenging task because of their soft and dynamic nature. In the present study, the morphology and dynamics of micrometer‐ and nanometer‐scale water‐containing compartments in ionic liquids were directly observed by electron microscopy. A variety of morphologies, including isolated droplets, dense structures, aggregates, and 2D meshworks, have been experimentally detected and studied. Using the developed method, the impact of water on the acid‐catalyzed biomass conversion reaction was studied at the microscopic level. The process that produced nanostructured domains in solution led to better yields and higher selectivities compared with reactions involving the bulk system.